The culture of keratinocytes and epidermal stem cells and their possible application in the treatment of chronic wounds - Pikuła, Michał; Imko-Walczuk, Beata; Nowacka-Pikuła, Danuta; Okuniewska, Aleksandra; Langa, Paulina; Jaśkiewicz, Janusz; Trzonkowski, Piotr (Dermatology Review/Przegląd Dermatologiczny, 2012)
Treatment of chronic wounds is still a serious problem in contemporary medicine. In the majority of cases it requires multi-disciplinary cooperation of specialized doctor and nursing teams and significant financial expenses. In many cases the conventional treatment of chronic wounds does not bring the expected therapeutic results, although new alternative therapeutic methods are being researched. One such method is the transplantation of in vitro cultured keratinocytes. The presented work focuses on methods of keratinocyte and epidermal stem cell culture, and the possibility of their transplantation. Safety aspects as well as the limitations of the analysed techniques are discussed. Also the authors present their experience concerning with epidermal cell culture for therapeutic purposes.